EFFECTS OF ADVERTISING CAMPAIGNS ON MARKETING PERFORMANCE (A STUDY OF NIGERIAN BOTTLING COMPANY PLC, ENUGU) - Godday, Luke Raymond (Advances in Social Sciences Research Journal, 2019)
ABSTRACT This study sought to evaluate the Effects of Advertising Campaigns on Marketing Performance, Nigerian Bottling Company Pic, Enugu. The general objective of this study was: to examine the effects of advertising campaign on marketing performance. The study employed descriptive research design using survey method. Data was collected through the primary and secondary source, whileprimary source data were from field survey which is questionnaire, the secondary were from already existing literatures like books and journals. The population here was made of Nigerian Bottling Company customers and consumers, the populationwas non-finite, as such, Fred and Williams formula was used, after pilot’s survey, to find the sample size of 323. The reliability of this study was determined with test and retest method at the value of 0. 83. Data were collated on tables and graphs. Chi-square was used in the test of hypotheses and Statistical Package for Social Sciences (SPSS) was used in the computation. The findings of the study revealed that advertising campaigns had significant effects on organizational performance, advertising media channels had significant influence on brand loyalty, advertising budgets had significant influence as an organization or company, one needs to pay recommends that in order to have a great performance as an organization or company, one needs to pay proper attention on advertising, if enough advertising is not done in an organization,the performance of that organization would be poor.Organizations should know that it is very necessary to evaluate an advertising campaign at the end of every advertising campaign. Organizations should know that an effective advert campaign evaluation is not only on the increase of sales but also on the awareness created and the relationship that has been established with the consumers for repeat purchase.